Pengaruh Promosi Jabatan Terhadap Kinerja Karyawan pada PT. Beringin Life di Jakarta - Rofiq Noorman Haryadi; Denok Sunarsi; Heri Erlangga; Nurjaya; Ana Wijandari (MAMEN: Jurnal Manajemen, 2022)
This study aims to determine the effect of promotion on employee performance at PT. Beringin Life in Jakarta. The method used is explanatory research with a sample of 60 respondents. The analysis technique uses statistical analysis with regression, correlation, determination and hypothesis testing. The results of this research variable of job promotion obtained an average score of 3,368 with good criteria. Employee performance variable obtained an average score of 3.833 with good criteria. Promotion has a positive and significant effect on employee performance with the regression equation Y = 9.840 + 0.846X, and the correlation coefficient is 0.705 or has a strong relationship with a determination value of 49.8%. Hypothesis testing obtained a significance of 0.000 <0.05.